From Balance to Rupture: Vaginal Microbiome in pPROM - Mrozek, Martyna; Blecharczyk, Małgorzata; Kamińska, Zuzanna Zofia; Zielińska, Agnieszka; Zydlewski, Igor; Pacanowska-Trawnicka, Martyna; Jakimowicz, Aleksandra; Malcher, Aleksandra (Journal of Education, Health and Sport, 2026)
PROM and its preterm form, pPROM, are major contributors to preterm birth and remain closely associated with serious maternal and neonatal complications. Growing evidence suggests that disruption of vaginal microbial homeostasis mayis closely linked to the pathogenesis of pPROM. In particular, the loss of protective Lactobacillus crispatus, accompanied by a shift toward Lactobacillus iners, anaerobic bacteria, and increased microbial diversity, appears to destabilize the vaginal ecosystem, promote local inflammation, activate matrix metalloproteinases, and ultimately compromise the structural integrity of the fetal membranes. Current empirical antibiotic therapy for pPROM does not account for interindividual variability in the vaginal microbiota and may paradoxically aggravate dysbiosis. In response to these limitations, emerging therapeutic strategies are increasingly focused on microbiota-targeted interventions, including personalized probiotic therapies, immunological and biological approaches, and vaginal microbiota transplantation. In addition, specific microbial signatures may serve as potential biomarkers of pPROM, thereby opening new avenues for personalized prevention and treatment. Although further prospective studies are required to validate the safety and efficacy of these emerging therapies, their potential already represents a promising direction for the future of modern perinatal medicine.